2015
DOI: 10.1016/j.exphem.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DOT1L and HOX gene expression in MLL-rearranged leukemia and beyond

Abstract: Leukemias harboring mixed lineage leukemia (MLL1) gene abnormalities are associated with poor clinical outcomes and new therapeutic approaches are desperately needed. Rearrangement of the MLL1 gene generates chimeric proteins that fuse the NH3-terminus of MLL1 to the COOH-terminus of its translocation partners. These MLL1-fusion oncoproteins drive the expression of homeobox genes such as HOXA cluster genes and MEIS1, which are known to induce leukemic transformation of hematopoietic progenitors. Genome-wide hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(101 citation statements)
references
References 166 publications
1
100
0
Order By: Relevance
“…289,290 Other examples are targeting of BRD4, a member of the BET family of bromodomain epigenetic readers, 291 or of KMT2A (MLL)-rearranged leukemias. 292,293 In a randomized trial conducted in patients with relapsed and refractory AML, the topoisomerase II inhibitor vosaroxin in combination with IDAC demonstrated a small survival benefit in patients older than 60 years (7.1 vs 5.0 months); a benefit was not shown in younger patients, potentially due to the higher transplant rate (45.8% ,60 years vs 20.2% $60 years). 222 Finally, targeted immunotherapy is an important novel approach.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…289,290 Other examples are targeting of BRD4, a member of the BET family of bromodomain epigenetic readers, 291 or of KMT2A (MLL)-rearranged leukemias. 292,293 In a randomized trial conducted in patients with relapsed and refractory AML, the topoisomerase II inhibitor vosaroxin in combination with IDAC demonstrated a small survival benefit in patients older than 60 years (7.1 vs 5.0 months); a benefit was not shown in younger patients, potentially due to the higher transplant rate (45.8% ,60 years vs 20.2% $60 years). 222 Finally, targeted immunotherapy is an important novel approach.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…Mechanistic insight into the underlying molecular basis of leukemogenesis driven by MLL1 fusions has expanded significantly within recent years (Cai et al 2015;Chen and Armstrong 2015). Wild-type MLL1 is a histone methyltransferase with specificity toward H3K4 and is required for the transcription of 1.8% of mammalian genes, including members of the homeobox (HOX) gene cluster (Rao and Dou 2015).…”
mentioning
confidence: 99%
“…Several chromatin-associated enzymes have been found to be required for the growth of MLL-rearranged leukemia, and small molecule inhibitors of some of these enzymes are promising candidates for the development of new drugs (Cai et al 2015;Chen and Armstrong 2015). The JMJD2 (also known as KDM4) enzymes are histone demethylases with specificity toward H3K9me3/me2 and H3K36me3/me2 (Cloos et al 2006;Fodor et al 2006;Klose et al 2006;Whetstine et al 2006).…”
mentioning
confidence: 99%
“…These differences may underlie the fact that only MLL1 is involved in chromosomal translocations in leukemia. The mechanisms by which MLL-fusion oncoproteins transform cells have been reviewed extensively [56][57][58][59], but the contribution of the non-translocated, wildtype allele remains controversial. Several early studies suggested that the remaining wild-type MLL1 molecule was required for maintaining MLL-AF9 initiated leukemia or that targeting the HMT activity of MLL1 would be therapeutically beneficial [60,61].…”
Section: Mll1 and Mll2 Functions In Leukemiamentioning
confidence: 99%